Pengaruh Teknik Peregangan PNF DYNAMIC STRECHING Dan DEPTH JUMP Dalam Meningkatkan Ketepatan SMASH Pada Siswa Ekstrakurikuler Bola Voli SMA Negeri 2 Palembang - M. Albar Abimayu; Rury Rizhardi; Mutiara Fajar (Lembaga Pengembangan Kinerja Dosen, 2024)
This experimental method is used to reveal whether or not there is an influence of the variables that have been selected for research. The population in this research is extracurricular students at SMA Negeri 2 Palembang, totaling 20 students. The sampling technique in this research uses the Total Sampling technique, namely the total of the population. Based on the results of research carried out at SMA Negeri 2 Palembang using these two exercises, the results of the t-test for the depth jump exercise show the conclusion that P (T<=t) two tail is 0.00000182. That means the value is significant 0.00000182 ≤ 0.05, so this result shows that there is a significant difference. This means that depth jump training affects the accuracy of volleyball smashes for extra-curricular students at SMAN 2 Palembang. Meanwhile, for the results of the pnf dynamic stretching exercise t-test, it can be seen that the conclusion of P (T<=t) two tail is 0.00072. That means the value is significant 0.00072 ≤ 0.05, so this result shows that there is a significant difference and means that depth jump training also influences the accuracy of volleyball smashes for extracurricular students at SMANEGERI 2 Palembang. Based on the results of the two exercises, the average (mean) data for the final test of the pnf dynamic stretching exercise was 17.5 and the average (mean) for the final test of the depth jump exercise was 16.5. Judging from the difference in the final test (post-test) of 1, depth jump training is more supportive and has a more significant effect than PNF dynamic stretching training on the accuracy of volleyball smashes for extracurricular students at SMA Negeri 2 Palembang.